KONSUMSI MADU HITAM MEMPERCEPAT PENYEMBUHAN LUKA PERINEUM PADA IBU MASA NIFAS - Siti Rusyanti; Nani Yuningsih; Ahmad Yani (Jurnal Penelitian Pendidikan IPA, 2024)
Perineal wound suturing is a common procedure during childbirth, affecting approximately 350,000 women annually in the UK and millions worldwide. Effective management of puerperal care with perineal sutures is critical to prevent infection and promote healing. This study examines the effect of black honey consumption as a complementary therapy to accelerate healing of grade II perineal wounds. Black honey’s antibacterial properties and cell regeneration capabilities support the wound healing process. The research was conducted at Mutiara Medika Clinic-Rangkasbitung in 2022 using a Control Group Posttest-Only design. A total of 38 postpartum mothers meeting the inclusion criteria were divided into intervention (n = 19) and control groups (n = 19). The intervention group consumed black honey in addition to standard puerperal care. Wound healing scores were assessed on days 3, 5, and 7. Statistical analysis revealed a significant improvement in wound healing for the intervention group compared to the control group (p = 0.003 and 0.000, respectively). The findings suggest that black honey consumption can serve as an effective complementary therapy to accelerate grade II perineal wound healing and reduce infection risk during the puerperium.